THE KEY DETERMINANTS OF INNOVATION IN SMALL AND MEDIUM SCALE ENTERPRISES IN SOUTHWESTERN NIGERIA - Dotun, Faloye Olaleye (European Scientific Journal, ESJ, 2015)
This paper examined the key determinants of innovation in small and medium scale enterprises (SMEs) in southwestern Nigeria. Data for the study were collected using questionnaire and face-to-face interview with SME Owners/Managers. A total of 1,247 questionnaires were administered on four lines of business using stratified random sampling of which 996 representing 51.18% were returned and found suitable for analysis. This was supplemented with interviews of 38 SME Owners/Managers. The data collected were analyzed using appropriate descriptive and inferential statistics. The study revealed that eight factors were accounted for technological and organisational innovation performance of SMEs in the study area. These factors included accessibility to foreign inputs, government support, relevant academic educational background of owner/managers, comparing company’s products regularly with those of its competitors, extent of investment in the Research and Development (R & D), extent of foreign collaboration/Number of external partners, prior experience of owner-manager, and availability of Patent and Copyright. In conclusion, the study found that accessibility to external inputs and extent of investment in the R & D are the most important factors that influence innovation in SMEs in southwestern Nigeria.